Development of the “Digihet” Multimedia Education Program to Improve Health Quality in the Setara Community Group - Nurhasanah Nurhasanah; Reza Andrea; M Ardan (Politeknik Pertanian Negeri Samarinda, 2024)
The digital divide and low health quality are challenges faced by the Setara South Sempaja community group. The impact of flooding is a health problem frequently experienced by this community group. The Technology and Health Education Program (Digihet) is designed to address this issue by providing education on the use of digital technology and clean and healthy living patterns to vulnerable groups affected by health problems. This study aims to develop and evaluate the effectiveness of the Digihet program in improving digital literacy, specifically in clean and healthy living patterns, and the quality of life of the community. The Digihet program is developed using multimedia development techniques, starting from the concept design stage to distribution. The Digihet program teaches about 10 clean and healthy living skills for households, including childbirth assisted by healthcare professionals, exclusive breastfeeding for babies, weighing babies and toddlers, using clean water, washing hands with clean water and soap, using healthy latrines, eradicating mosquito larvae at home, eating fruits and vegetables every day, engaging in physical activity every day, and not smoking indoors. Data were collected through beta testing, and the research results showed that the Digihet program is effective in increasing digital literacy in forming clean and healthy living patterns. The results of this study are expected to serve as a basis for developing multimedia health education programs and contribute to enhancing the understanding of the relationship between digital literacy, public health, and information technology in the context of household health quality.